Development of Helisoma trivolvis pond snails as biological samplers for biomonitoring of current‐use pesticides. (21st June 2016) - Morrison, Shane A.; Belden, Jason B.
Abstract: Nontarget aquatic organisms residing in wetlands are commonly exposed to current‐use pesticides through spray drift and runoff. However, it is frequently challenging to measure exposure because of rapid dissipation of pesticides from water and reduced bioavailability. The authors' hypothesis is that freshwater snails can serve as bioindicators of pesticide exposure based on their capacity to passively accumulate tissue residues. Helisoma trivolvis snails were evaluated as biomonitors of pesticide exposure using a fungicide formulation that contains pyraclostrobin and metconazole and is frequently applied to crops surrounding depressional wetlands. Exposure–response studies indicate that H. trivolvis are tolerant of pyraclostrobin and metconazole at concentrations >10 times those lethal to many aquatic species, with a median lethal concentration based on pyraclostrobin of 441 μg/L (95% confidence interval of 359–555 μg/L). Bioconcentration factors ranged from 137 mL/g to 211 mL/g and from 39 mL/g to 59 mL/g for pyraclostrobin and metconazole, respectively. Elimination studies suggested one‐compartmental elimination and snail tissue half‐lives ( t 50 ) of approximately 15 h and 5 h for pyraclostrobin and metconazole, respectively. Modeling derived toxicokinetic parameters in the context of an environmentally relevant pulsed exposure suggests that residues can be measured in snails long after water concentrations fall below detection limits. With high fungicide tolerance, rapid accumulation, and slow elimination, H. trivolvis may be viable for biomonitoring of pyraclostrobin and should be investigated for other pesticides. Environ Toxicol Chem 2016;35:2320–2329. © 2016 SETAC